THE GRADUATES’ PERCEPTION TOWARDS PERSONAL CHARACTERISTICS REQUIREMENT IN JOB SEEKING PROCESS IN HIGHER EDUCATION INSTITUTION - Harry Widyantoro (Universitas Hayam Wuruk Perbanas, 2010)
Personal quality is generally needed in the companies such as the spirit of work, ambition, and ability to take challenges. Previous studies also assert that various companies had evaluated in different way towards the characteristics of personal quality. The purpose of this research is to identify the quality of the personal characteristics required by the company for university graduates. Besides that, this research also measures by evaluating the graduates (job seekers)’ quality of the personal ability that they have obtained from the learning process in universities, and to see the graduates’ perception of the importance of personal abilities against job search process. Respondents in this research were graduates of various higher education institutions in East Java which were looking for job vacancies. Data collection was done using questionnaire distributed to the respondents of about 346 graduates. Sampling technique used was convenient sampling method. Utilizing of this research, higher education institution can the personal qualification required by the company and the students’ perception conduct the evaluation of process and methods of learning in relation to the building of the graduate’s personal qualification and minimize the gap between on their personal qualification. The results are expected to have some implications for HEIs